UNLOCKING THE POWER OF DATA: EFFECTIVE DATA-DRIVEN MARKETING STRATEGIES TO ENGAGE MILLENNIAL CONSUMERS - Benediktus Rolando; Herry Mulyono (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
As the marketing landscape continues to evolve, data-driven strategies have emerged as a critical component in effectively reaching and engaging with the millennial consumer demographic. In the age of big data, data driven marketing has become a powerful tool for businesses seeking to gain a competitive edge and optimise customer engagement. This paper provides a comprehensive literature review on effective data-driven marketing strategies to reach millennial consumers. It explores the use of big data and social relationship maps to identify key influencers and leverage their reach for exponential information dissemination. Additionally, the review examines various approaches and tactics for engaging with millennial consumers using data-driven techniques. Key findings suggest that effective data-driven marketing strategies can significantly enhance consumer engagement, brand loyalty, and overall marketing effectiveness. The paper aims to provide insights and understanding of the current research and best practices in data-driven marketing strategies for targeting the millennial demographic.